Evaluación del comportamiento agronómico de dos variedades de avena (Avena sativa L.) INIAP-Fortaleza 2020 e INIAP-82 bajo la aplicación de lactofermento (Suero de leche) en las condiciones ambientales del Campus Salache UTC 2021-2022. - Caiza Jaguaco, Adriana Michelle (2022)
The present investigation was carried out in the Salache Sector, Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, at an altitude of 2,750 m above sea level, cold temperate dry climate,temperature 13.2 °C, relative humidity 82%, rainfall (mm) 0,7 The objective was to determine the adaptation of two oat varieties (Avena sativa L.) INIAP-Fortaleza 2020 and INIAP-82, under the application of lactoferment. The modality of the research is experimental where two oat varieties were used with the application of lactoferment (milk whey), the experimental design implemented was in divided plots (A x B) obtaining 4 treatments with 4 replications where the following variables were analyzed: germination percentage, growth habit, cover, height, green matter, and grain yield, in addition the chemical analysis of the lactoferment was performed, obtaining the following results. The variety with the best agronomic performance under the environmental conditions of the Salache campus is oats INIAP-Fortaleza 2020 with 110.28 cm at 107 days, the one with the highest percentage of coverage at 30 days was treatment T1 (INIAP-Fortaleza 2020), with 97.75%, according to the Tukey tests at 5%, a significant difference can be determined between varieties, obtaining the highest yield in the oat variety INIAP-Fortaleza 2020 with 4687.5 kg*ha-1. The chemical composition of the serum shows microelements, Fe (3ppm), Zn (0.20pom) and macroelements, Na (791ppm), K (1547 ppm), Ca 362 (ppm), P(468 ppm), Mg (78 ppm), which act as fertilizers for plant development, with a dose of 75% water and 25% serum.